Flexible fluorescent films based on quantum dots (QDs) and natural rubber - Danna, Caroline Silva [UNESP]; Osorio-Román, Igor [UNESP]; Dognani, Guilherme [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP]; Agarwal, Vivechana; Job, Aldo Eloizo [UNESP] (Wiley, 2017)
This article presents the fabrication and characterization of polyisoprene fluorescent films doped with CdTe quantum dots (QDs). The biopolymer (polyisoprene) is extracted from natural rubber latex, generating flexible and transparent films in visible range (transmittance over 90%) ideal as a matrix to support QDs. The water solubility of the biopolymer facilitates its doping with water dispersed QDs at room temperature to obtain the fluorescent films. Thermogravimetric analysis reveals that QDs have no significant effect on the thermal properties of the biopolymer. Photophysical characterization of the solution and solid state (films) of the QDs evidenced that the polymer matrix does not influence its emission properties, the maximum fluorescence peaks have only 2 nm of difference between the solution and solid state (films) samples. Therefore, polyisoprene from natural rubber can be considered as an excellent flexible matrix to fabricate fluorescent films with QDs. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45459.
Keywords: biopolymers and renewable polymers; nanoparticles; nanowires and nanocrystals; optical properties; separation techniques; thermogravimetric analysis